Applying Butterfly Method in the Learning of Addition and Subtraction of Fractions - Laidin, Dalilah Rauqah; Tengah, Khairul Amilin (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2021)
Several researches attempt to improve the performance in addition and subtraction of fraction by focusing on students’ understanding, such as applying fraction tiles manipulatives and number line in the teaching, or using visual aids such as area model and drawings or virtual diagrams. Similarly, few studies focus on adopting simple procedures that will facilitate students in attempting the topic. Butterfly Method is an approach that not only simplifies the pedagogical approach of learning addition and subtraction of fraction, but also indirectly promotes students’ conceptual understanding in the topic. Yet this approach is not commonly practiced in Brunei. This action research employed quantitative approach involving fourty-one Year 9 IGCSE level students from a government secondary school in Brunei Darussalam. The study aimed to investigate the effect on applying Butterfly Method in the learning of addition and subtraction of fraction through pre-test and post-test. The study revealed a significant improvement in students’ performance through Wilcoxon Signed rank test (Z = 4.2332, p-value < 0.05), with large effect size (r = 0.6611). This is also supported with the improvement of the overall mark distribution of students from pre-test to post-test, with Hake’s normalised gain values indicated majority of the participants achieved high (56.1%), medium (7.32%) and low (2.44%) improvements. Item analysis also indicated overall improvement of correct attempts in questions related to addition and subtraction of fraction, most apparently on fraction problems involving denominators not multiple of each other, improper fractions and mixed numbers. Thus, applying Butterfly Method significantly improved the overall students’ performance in the learning of addition and subtraction of fractions. DOI: https://doi.org/10.22342/jpm.15.2.13934.161-174